Mechanism of equipment selection for different types of production - E. B. Mazurin; E. V. Savenko (Омский научный вестник)
Companies engaged in production of products have a high uncertainty in the choice of technological equipment. The production facilities of an enterprise can consist of both its own technological equipment and equipment taken on lease. In addition, you can use a subcontract for the production of products. The criteria for choosing technological equipment can be: characteristics of the products and the expected premium to the production cost. The development and further use of a mechanism for selecting technological equipment for a single type of production can increase the efficiency of production processes.